Evaluating project achievement of the ITSP implementation - Jusoh, Yusmadi Yah; Hamdan, Abdul Razak; Deraman, Aziz (2007)
Over the years most of the organization has establish their information technology strategic planning (ITSP). The purposes are to justify the efficiency, effectiveness and competitiveness of the information technology (IT). However, the challenge is to make sure the ITSP successfully implemented. Nowadays, measuring the performance of the ITSP implementation is a considerable interest to indicate the effort is worth or need to be evaluated for improvement. The successfulness of the ITSP implementation stage is important to make sure the planning of IT resources and project are properly organized. The focus of this paper is on evaluating the performance of the IT project involves in the ITSP implementation. Thus, measurement methodology was proposed to justify the project achievement through the weight scoring method and calculation formulas. The performance evaluation were based on the proposed key performance indicator and related stage of the project management life cycle.